HDAC6 Inhibition Protects against OGDR-Induced Golgi Fragmentation and Apoptosis - Jie Zhang (Oxidative Medicine and Cellular Longevity, 2019)
The Golgi apparatus (GA) is a pivotal organelle, and its fragmentation is an essential process in the development of apoptosis. GA is a potential target in the treatment of cerebral ischemia-reperfusion injury. Histone deacetylase 6 (HDAC6) catalyzes the removal of functional acetyl groups from proteins and plays an important role in cell homeostasis. In this study, the neuroprotective effects and the underlying mechanisms of HDAC6 inhibition were assessed in an ischemia-reperfusion injury model. Mouse neuroblastoma N2a cells and cultured neurons were subjected to oxygen-glucose deprivation/reperfusion (OGDR) insult. OGDR induces Golgi fragmentation and reduces tubulin acetylation in N2a cells and cultured neurons. Golgi fragmentation is prior to nuclear chromatin condensation after OGDR injury. Overexpression of GBF1 not only protects against OGDR-induced Golgi fragmentation but also protects against OGDR-induced apoptosis, suggesting that Golgi fragmentation is not secondary to apoptosis but plays a causal role for subsequent apoptosis. HDAC6 inhibition suppresses OGDR-induced tubulin deacetylation, p115 cleavage, and caspase 3 activation and protects against OGDR-induced Golgi fragmentation and apoptosis. This work opens a new avenue for potential clinical application of HDAC6 inhibitors for cerebral ischemia-reperfusion-related disorders.